Pengaruh CSR Terhadap Niat Bergabung Generasi Milenial untuk Bekerja di PT Telkom Indonesia Tbk - Heriyanto, Rudi; Sugiyanto, Sugiyanto (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The complex, competitive, and ever-changing operational conditions and stakeholder expectations that characterize the business environment have motivated organizations to utilize social responsibility (CSR) as a strategic instrument that marks them as employers of quality employees. Some of the companies can carry out CSR well; one of these companies is PT Telkom Indonesia Tbk. This research uses the associative method. The data collection technique uses primary data as a result of distributing questionnaires using the Google form. The population in this study is all residents who are looking for work in the DKI Jakarta area who feel the implementation of CSR carried out by PT Telkom Indonesia Tbk. The sample method used in this research is non-probability sampling, with the sampling technique being purposeful sampling. There are 4 variables in this study, where the independent variables are CSR (X1), altruism (X2 Moderation), and organizational attractiveness (X3 Moderation), and the dependent variable is intention to join (Y). This measurement uses a Likert scale with a scale of 1–5. Data processing uses IBM SPSS version 23. Based on the results of hypothesis testing in this study, CSR (X1) has a positive and significant effect on intention to join (Y). The altruism variable (X2) does not strengthen the effect of CSR (X1) on intention to join (Y). Organizational Attractiveness Variable (X3) strengthens the effect of CSR (X1) on Intention to Join (Y). CSR, which is moderated by the attractiveness of a good organization, can increase the interest of the millennial generation in joining the workforce.